Assessing post-exercise respiratory gas kinetics in clinical sample - a pilot study. (11th May 2021) - Patti, A; Blumberg, Y; Moneghetti, KJ; Neunhaeuserer, D; Haddad, F; Myers, J; Ashley, E; Christle, JW
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiopulmonary exercise testing (CPX) is established in the evaluation of patients with cardiac and pulmonary diseases, and its clinical utility seems to be expanding. Currently the most important diagnostic and prognostic ventilatory metrics of CPX rely on the exercise phase. Nevertheless, a consistent body of evidence suggests that important information can be derived from the recovery phase, especially in the first few minutes after exercise. In this context, patients with heart failure (HF) demonstrate a slower recovery of the oxygen consumption (VO2) compared with healthy individuals. Purpose: To comprehensively investigate the behavior of respiratory gases during recovery from CPX in a diverse cohort of HF patients. Methods: All individuals who performed CPX at the department of cardiology of Stanford University Hospital were eligible for the study. Patients were included in the experimental group if they (i) were recorded for five minutes after the exercise phase of CPX and (ii) had documented heart failure. They were excluded if they had other clinical diagnoses which may be responsible for exercise intolerance or symptoms or were unable to give informed consent. Healthy controls were recruited from the local community and were included if they did not have documented or suspected disease. Respiratory gases were collected on a breath-by-breath basis and analysed after applying a 30 second rolling average filter. Metrics were analyzed as absolute values, percentage change from peak and the half-time of recovery (T ½; i.e. the duration until a metric had returned to ½ of its value at peak). Data was analyzed over time within patients and averages between groups using parametric statistical methods. In accordance with previous studies, the amount of change in a metric after exercise is presented as the "magnitude" of overshoot. Results: 32 patients with HF (11 Female, 47 ± 13 yrs) and 30 healthy subjects (14 Female, 43 ± 12 yrs) were included. A comparison of ventilatory metrics during recovery between HF and controls is depicted in Figure 1. Peak VO2 was 1135 ± 419 mL/min (13.5 ± 3.8 mL/Kg/min) vs 2408 ± 787 mL/min (32.5 ± 9.0 mL/Kg/min); P <0.01. A significant difference between patients with HF and healthy subjects was found in T ½ of VO2 (111.3 ± 51.0s vs 58.0 ± 13.2s, p < 0.01) and VCO2 (132.0 ± 38.8s vs 74.3 ± 21.1s, p < 0.01). The magnitude of the overshoot was also found to be significantly reduced in patients with HF for VE/VO2 (41.9 ± 29.1% vs 62.1 ± 17.7%, P < 0.01), RQ (25.0 ± 13.6% vs 38.7 ± 15.1%, p < 0.01) and PETO2 (7.2 ± 3.3% vs 10.1 ± 4.6%, p < 0.01). Finally, the magnitude of the RQ overshoot showed a moderate correlation with peak VO2 (ϱ=0.58, p < 0.01). Conclusions: We observed that ventilatory kinetics measured in early recovery after CPX differ significantly between healthy subjects and patients with HF. The assessment of post exercise respiratory gases in a clinical setting may add to the prognostic and diagnostic value of CPX in heart failure.